The State's Obligation in Providing Replacement Housing Due to Lost Land - Milda Milda; Nia Kurniati; Yani Pujiwati (Eduvest - Journal of Universal Studies, 2024)
This research aims to find out the state's obligation in organizing occupancy lost due to land destruction. The form of this research is normative juridical with a statute approach and case approach. The type of research used is descriptive research and the data used is secondary data which is then All data obtained is collected and analyzed normatively qualitative. The results showed that the impact of the loss of land was that the community lost their shelter. Shelter is a basic right of all citizens, especially those affected by the disaster. The state is responsible for the fulfillment of the basic rights of the community, namely organizing and providing housing / shelter that is feasible and safe from disasters.  If the state is absent then the state is violating the mandate of the Constitution and Pancasila.